2016
DOI: 10.1167/iovs.15-18713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Choroidal Thickness in Children With Iron Deficiency Anemia

Abstract: The patients with IDA had significantly thinner choroidal thicknesses than those of the healthy children. Choroidal thinning in childhood may be an early sign of deterioration in the ocular blood circulation, without any risk of atherosclerosis in advanced age in the patients with IDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…Egzersiz, gebelik, erkek cinsiyet, sildenafil kullanımı, prediyabetik retinopati, çocukluk çağı obesitesinin koroid kalınlığını artırdığı bildirilmiştir (12)(13)(14)(15)(16)(17) . Konjestif kalp yetersizliği, karotis stenozu, sigara, kahve, ileri yaş, çocuklarda demir eksikliği anemisi, diyabetik makülar ödem ve proliferatif diyabetik retinopatinin eşlik ettiği diyabetin koroid kalınlığını azalttığı bildirilmiştir (7,(18)(19)(20)(21)(22) . Yüksek myopiye neden olan aksiyel uzunluk artışı ve yaşa bağlı koroidal atrofi koroid kalınlığını azaltan oküler nedenlerdir (23,24) .…”
Section: Discussionunclassified
“…Egzersiz, gebelik, erkek cinsiyet, sildenafil kullanımı, prediyabetik retinopati, çocukluk çağı obesitesinin koroid kalınlığını artırdığı bildirilmiştir (12)(13)(14)(15)(16)(17) . Konjestif kalp yetersizliği, karotis stenozu, sigara, kahve, ileri yaş, çocuklarda demir eksikliği anemisi, diyabetik makülar ödem ve proliferatif diyabetik retinopatinin eşlik ettiği diyabetin koroid kalınlığını azalttığı bildirilmiştir (7,(18)(19)(20)(21)(22) . Yüksek myopiye neden olan aksiyel uzunluk artışı ve yaşa bağlı koroidal atrofi koroid kalınlığını azaltan oküler nedenlerdir (23,24) .…”
Section: Discussionunclassified
“…IDA is the most frequent and treatable anemia worldwide (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The prevalence of IDA is higher in women, especially in premenopausal women and uncommon in adults (1, 2, 14).…”
Section: Discussionmentioning
confidence: 99%
“…of hypoxia, detrimental effects can be seen in various systems of the body including ocular structures through enhancement of effects of ischemia (5). Several studies have shown the effect of iron deficiency on ocular structures, especially focused on the posterior segment of eye (6)(7)(8)(9)(10). However, a recent study evaluating the anterior segment focusing on endothelial cells showed significant changes at IDA (9).…”
mentioning
confidence: 99%
“…We planned our study of a continuous response variable from independent control and experimental subjects with one control(s) per experimental subject. In a previous study 12 the response within each subject group was normally distributed with standard deviation 39.77. If the true difference in the experimental and control means was 30.54, we needed to study at least 28 experimental subjects and 28 control subjects to be able to reject the null hypothesis that the population means of the experimental and control groups are equal with probability (power) 0.8.…”
Section: Sample Size Calculationsmentioning
confidence: 99%
“…In recent studies, central corneal thickness (CCT) and choroidal thickness were found to be decreased in children with sickle cell anemia and iron deficiency anemia (IDA). 11 , 12 In the present study, the CCT, specular microscopic measurements, the thickness of retinal nerve fiber layer (RNFL), and the thickness of ganglion cell-inner plexiform layer (GC-IPL) were compared between the females with IDA, combined IDA and vitamin B12 anemia (B12DA), and healthy females.…”
Section: Introductionmentioning
confidence: 99%